Influences of Seaways, Atmospheric CO2 and Greenland Ice Sheet on the Pliocene Climate in the Kiel Climate Model - Song, Zhaoyang (2017)
This thesis provides an improved understanding of the impacts of changes in the atmospheric CO2-concentration, oceanic seaways, and Greenland ice sheet (GrIS) on the Pliocene climate (5.3-2.6 million years before present; Ma B.P.). Three sets of sensitivity experiments using a coupled atmosphere–ocean–sea ice model are analyzed and assessed with multiple paleoclimate reconstructions for the Pliocene. In particular, in the first set the model sensitivity of sea surface temperature (SST) and the East Asian summer monsoon (EASM) to changes in CO2 and oceanic seaway is investigated, while in the second set the mean state, the annual cycle in the tropical Pacific and El Niño/Southern Oscillation (ENSO) is analysed. In the third set, the impact of GrIS changes on the response of the Atlantic meridional overturning circulation (AMOC) and surface climate to obliquity forcing is examined.